Understanding national biodiversity targets in a REDD+ context. Issue 92 (February 2019) - Johnson, Brian Alan; Dasgupta, Rajarshi; Mader, André Derek; Scheyvens, Henry
Highlights: Scenario analysis to assess national biodiversity targets' benefits in REDD + terms. Proposed approach found to be possible for 16 developing countries. Case studies conducted for Cambodia and Lao PDR. Achieving Cambodia's deforestation target reduces emissions by ∼40 MtCO2 /year. Achieving Lao PDR's reforestation target results in ∼836 MtCO2 of avoided emissions. Abstract: Forest conservation is a key component of multilateral environmental agreements related to biodiversity conservation (Convention on Biological Diversity; CBD)) and climate change (UN Framework Convention on Climate Change; UNFCCC), and ambitious national commitments are essential to the implementation of these agreements. To understand the relationships between developing countries' different forest conservation commitments/policies made under the CBD and UNFCCC, here we proposed a policy screening scenario analysis approach. Two alternative scenarios of future forest changes are generated at the national scale: one based on a country's national biodiversity targets developed for the CBD, and another based on the country's REDD + forest reference level (FRL) developed for the UNFCCC. The proposed scenario analysis allows for estimation of the climate change mitigation and natural forest conservation benefits of selected national biodiversity targets in terms directly relevant to REDD+ (i.e. in relation to the "baseline" scenario of the FRL). From a literature review of national submissions to the CBD and UNFCCC, we found this scenario analysis is currently feasible for 16 countries. As case studies, we performed the scenario analysis for one country with a deforestation-related target (Cambodia) and one country with a reforestation-related target (Lao PDR) to illustrate the methodology in detail. We found that achieving Cambodia's NBT of reducing natural forest losses by 50% would lead to a reduction of net natural forest losses by 145, 767 ha./year and net CO2 emissions by 39, 742, 511 tons/year (considering above-ground and below-ground biomass), while the achievement of Lao PDR's NBT of increasing forest cover to 70% of the national land area would result in a total of 3, 216, 588 ha. of net natural forest gains and a total of 836, 386, 724 tons of avoided CO2 emissions (considering above-ground and below-ground biomass).